THE VALIDITY DEVELOPMENT OF ADOBE FLASH BASED LEARNING MEDIA AT ENERGY CONVERSION MACHINE COURSE IN VOCATIONAL EDUCATION PROGRAMS - Hasanah, Uswatun; Jalinus, Nizwardi; Maksum, Hasan (Journal of Education Research and Evaluation, 2019)
Learning outcomes of Diploma 3 students of Mechanical Engineering in the Energy Conversion Engineering course seem not optimal, it estimated that the learning outcomes were not optimal due to the inaccurate use of learning media in the learning process. The purpose of this study was to produce a valid adobe flash based learning media.This research was Research and Development (R&D) method with ADDIE model. The research subjects were students of the Diploma 3 Mechanical Engineering who took Energy Conversion Engineering courses. Data collect in the form of questionnaire sheets and primary data were obtained from lecturers and students. Data were analyzed by descriptive analysis technique by describing validity of adobe flash based learning media. Based on the analysis of the data obtained the validity of adobe flash based learning media, declared valid on the Content aspect with score 0,85 and the Display aspect with score 0,91. Based on the findings of this study it was concluded that the adobe flash based learning media was valid as a learning media in the Energy Conversion Machine course.